Professionalism and Management of Steam Education in Nigeria - Abdullahi, Nimota Jibola K. (NIU Journal of Social Sciences, 2018)
This study investigated professionalism and management of STEAM education in Nigeria. The purpose of this study is to examine the relationship between teacher commitment to students, parents, community and effective management of STEAM education in Nigeria. To achieve the purpose of this study, three hypotheses were formulated and tested. Quantitative research design was used for the study. A self-designed questionnaire titled â€œProfessionalism and Management of Steam Education Questionnaireâ€ (PMSEQ) was used to collect data for the study. The population of this study comprised all 310 principals in public senior secondary schools in Kwara State. Sample of 175 principals were selected with the use of Research Advisor (2006) table of determine sample size of a known population. Thus, stratified random sampling technique was used to select principals from the sample schools. This was to ensure that all categories of principals were given equal chance of being selected for the study. The data collected were analyzed using Pearson product moment correlation coefficient statistics. All hypotheses were tested at 0.05 level of significance. The result revealed that there was a positive and significant relationship between teacher commitment to students, parents, community and effective management of STEAM education in Nigeria. It was recommended that teacher should continue to improve their commitment to students by dealing justly and impartiality with students, avoidance of damaging comments with the learners as well as planning the lesson by taking into account specific interest of the learners. Teachers should also ensure effective commitment to parents by establishing friendly and cooperative relationship with home of students, provide parents with information that will improve the performance of students positively, as well as keeping parents informed about the progress of their children in school. Lastly, teacher should continue their commitment to community so as to strengthening the community moral and intellectual life, keep the community informed of the educational teacher programme which is being provided, and help the school to adhere to reasonable pattern of behaviour accepted by the community in order to achieve effective management of STEAM education in Nigeria. Keywords: professionalism, management, STEAM education, Nigeria